Associations between timing and quality of solid food introduction with infant weight-for-length z-scores at 12 months: Findings from the Nurture cohort. (1st October 2019) - Vadiveloo, Maya; Tovar, Alison; Østbye, Truls; Benjamin-Neelon, Sara E.
Abstract: This study assesses associations of the timing and quality of solid foods introduced during infancy with weight-for-length (WFL) z -scores at 12 months within the Nurture cohort. Women from North Carolina self-reported sociodemographics, the timing and type of solid food introduction, and reasons for introducing solids; infant anthropometrics were measured every 3 months through 1 year (n = 666). Frequency (0–5x/day) infants consumed fruits and vegetables was used to compute a mean (4–12 months) healthy food score (HFS), and sweets, french fries, snacks, and ice cream was used to compute a mean unhealthy food score (UnHFS). Multivariable-adjusted generalized linear models were used to examine the relationship of early solid food introduction, HFS quartiles (Q), UnHFS quartiles, and interactions between these variables with WFL z -scores at 12 months (n = 449). Exploratory analyses evaluated WFL z -scores among 4 groups of infants with high/low HFS and high/low UnHFS. On average, mothers were 28 years with a pre-pregnancy BMI of 30.5 kg/m 2 ; 65% were Non-Hispanic Black, and 59% had incomes <$20, 000. Mean HFS and UnHFS were 2.4 (range 0–7.4 of 10) and 1.8 (range 0–9.9 of 20), respectively. Nearly 1/3 of mothers introduced solids early, but early introduction and the HFS were not associated with WFL z -scores. Infants in Q3 and Q4 of the UnHFS had higher WFL z -scores (0.75–0.79 ± 0.09) compared to infants in Q1 (0.42 ± 0.0.9), p < 0.05. Frequent unhealthy food intake was associated with higher WFL z -scores at 12-months, underscoring the importance of reducing unhealthy food intake in the first year.